Über den russischen Südländer –: Zur Funktion der Krim als russischer Süden und des južanin (Südländers) im russischen Krim-Diskurs des Zarenreichs - Jobst, Kerstin Susanne (Comparativ, 2009)
As cultural studies have shown, the South is – like the East or the Orient - more than simply a magnetic orientation. The South stands simultaneously for both backwardness and passivity whilst also for authenticity, naturalness, and an exotic touch. The same is also true for the Russian colonial discourse of the Crimean peninsula which was annexed in 783. This article describes and analyses the ambiguity of the recording of the Crimean South in colonial debates: The Northern Russian power, located in the cold, attempted to ´find´ a warm and beautiful supplement on the peninsula. Moreover the annexing of the peninsula was also intended to demonstrate the Russian ability to ´civilise´ the ´backward´ former Crimean Khanate with its Muslim population.